Bengkel Inggris Program For Enhancing English Potencial - Fitri Ayu; Devi Anggriani; Nizamuddin (International Forum of Researchers and Lecturers, 2023)
The era of rapidly developing scientific and technological progress has opened up opportunities for international communication through English. The study was conducted to analyze the potential of elementary school students in English skills in Klambir Lima Kebun Village. Realizing this reality, the